Co-expression of ApGSMT2g and ApDMT2g in cotton enhances salt tolerance and increases seed cotton yield in saline fields. (September 2018) - Song, Jiuling; Zhang, Rui; Yue, Dan; Chen, Xiugui; Guo, Zhiqiang; Cheng, Cheng; Hu, Minghui; Zhang, Juren; Zhang, Kewei
Highlights: Co-expressing ApGSMT2g and ApDMT2g in cotton elevates glycine betaine levels above the naturally produced content. Co-expressing ApGSMT2g and ApDMT2g in cotton enhances salt tolerance both in the greenhouse and in saline fields. Co-expressing ApGSMT2g and ApDMT2g in cotton increases seed cotton yield in saline fields. Transgenic ApGSMT2g and ApDMT2g cotton maintains intracellular osmoregulation and K + /Na + homeostasis under salt stress. Transgenic ApGSMT2g and ApDMT2g cotton shows better performance of PSII and greater photosynthetic capacity than wild-type under salt stress. Abstract: Salinity is a major factor limiting plant growth and agricultural production worldwide. Glycine betaine (GB) is one of the most universal osmoprotectants that protects plants from environmental stresses. In this study, transgenic cotton co-expressing ApGSMT2g and ApDMT2g was generated by Agrobacterium -mediated transformation. Compared with wild-type (WT), co-expression of ApGSMT2g and ApDMT2g in cotton results in higher GB amounts, higher relative water content (RWC), lower osmotic potential, more K +, and less Na + under salt stress, which contributes to maintaining intracellular osmoregulation and K + /Na + homeostasis and thus confers higher salt tolerance and more vigorous growth. Furthermore, co-expressing ApGSMT2g and ApDMT2g in cotton leads to better performance of PSII, greater photosynthesis capacity, and finally, improves plant growth and increases cotton seed yield compared to WT under salt stress. The reason for the better performance of PSII in transgenic cotton is the higher quantum yield and a more reasonable quantum ratio distribution than WT under salt stress. Co-expressing ApGSMT2g and ApDMT2g in cotton also reduces membrane damage and increases superoxide dismutase (SOD) activity compared to WT under salt stress. Our results indicate that transgenic ApGSMT2g and ApDMT2g cotton shows higher salt tolerance and more seed cotton yield in saline fields compared to wild-type.